2021
DOI: 10.3390/w13111482
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Runoff and Evaporation Assessment Methods to Evaluate Wetland–Groundwater Interaction in Mediterranean Evaporitic-Karst Aquatic Ecosystem

Abstract: This work compares the applicability of several free-surface evaporation and runoff equations in simulating water level variations of small Mediterranean wetlands. The Amarga and Jarales wetland are two pilot sites with an evaporite-karst genesis located in southern Spain. The water level was continuously recorded in both wetlands, and exhaustive weather monitoring was performed. The combined datasets have permitted quantification of the surficial elements of their water budget (precipitation, runoff, and evap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Laguna Amarga, which takes its name from the bitter taste of its water owing to the high concentration of magnesium sulfate it contains, is a permanent saline lake, unlike the very close Laguna Dulce, which is a temporary and non-saline lagoon. This enclave is located on rocky outcrops composed mainly of clays, evaporite rocks (gypsum, anhydrites, and halites), marls, dolomites, and sandstones embedded in a Triassic matrix (Vera & Martín-Algarra, 2004;Gil-Márquez et al, 2021). The vegetation on the slopes surrounding the lake consists of a mosaic of olive groves and other natural vegetation consisting of Mediterranean shrubs belonging to Pistacio lentisci-Rhamnetalia alaterni Rivas-Martínez 1975and Rosmarinetalia officinalis Br.-Bl.…”
Section: Resultsmentioning
confidence: 99%
“…Laguna Amarga, which takes its name from the bitter taste of its water owing to the high concentration of magnesium sulfate it contains, is a permanent saline lake, unlike the very close Laguna Dulce, which is a temporary and non-saline lagoon. This enclave is located on rocky outcrops composed mainly of clays, evaporite rocks (gypsum, anhydrites, and halites), marls, dolomites, and sandstones embedded in a Triassic matrix (Vera & Martín-Algarra, 2004;Gil-Márquez et al, 2021). The vegetation on the slopes surrounding the lake consists of a mosaic of olive groves and other natural vegetation consisting of Mediterranean shrubs belonging to Pistacio lentisci-Rhamnetalia alaterni Rivas-Martínez 1975and Rosmarinetalia officinalis Br.-Bl.…”
Section: Resultsmentioning
confidence: 99%
“…This ultimately confirms the spatiotemporal relationship between meteorological factors and the spatial distribution of natural wetlands during the wetland recovery period. During this period, the wetland area in the Northeast Plain of China increased by 37.76 × 10 3 km 2 , possibly due to the increased surface runoff replenishment caused by abundant precipitation and balanced temperature, and the reasonable transpiration promoted the energy cycle of the natural wetland aquatic ecosystem, triggering a new round of natural wetland self-ecological restoration [81][82][83]. From the perspective of topographic factors, the uneven distribution of elevation can lead to changes in surface water runoff direction, thereby affecting the spa- In addition, natural factors consisting of meteorological and topographic factors also have a certain driving effect on natural wetlands.…”
Section: Main Driving Force Of Natural Wetlandmentioning
confidence: 99%
“…The acquisition of these data typically requires a multidisciplinary study approach that includes using more specialized investigation methods to estimate the recharge or contributing areas of karst springs (Ginsberg & Palmer, 2002). Recent research also showed that if hydrogeological context in karst area wants to be fully understood, it is necessary to control hydrological factors which affect its water budget (Gil-Márquez et al, 2021), while the identification of recharge areas of karst aquifers can enable sustainable management of groundwater resources (Iacurto et al, 2021). It was shown that inclusion of different tracers in monitoring can greatly reduce ambiguity of interpretation, but also that complete certainty in hydrogeology research of karst aquifers is still very hard to achieve (Stroj et al, 2020).…”
Section: Introductionmentioning
confidence: 99%